Human capital futures: an educational perspective - Chris Bottrill (Journal of Tourism Futures, 2022)
Purpose – Education institutions can be slow to react to the changes that are happening in human capital development content and delivery. This article highlights some of the shifts that robotics, artificial intelligence (AI) and access to information are having on jobs in tourism and the future of work. It explores the ways in which the tourism education sector can respond. Design/methodology/approach – This paper draws upon content shared at several conferences and webinars addressing the future of work and the education delivery methods from experts and commentators on the subject. This was augmented by research conducted by global tourism associations, the World Economic Forum and other global associations and supported with secondary data from recent media and online content providers. Findings – By highlighting emerging trends in the sector and skills to thrive in the fourth industrial revolution, we can identify what education should focus on during this period of transition and uncertainty. We need to capitalize on the digital delivery skills we have developed due to COVID-19 and build new content and accessible learning approaches. Originality/value – There are many uncertainties about the future of work and the way that a rapidly digitized education delivery approach has and will affect tourism education in the future. This article is aimed to generate further thought and dialogue by identifying changes and raising points about what we are effective at in public post-secondary education and what we need to capitalize on and adapt to in the future. The core question posed is that if the tourism and hospitality workforce and work environment has changed, has, or can, tourism and hospitality training and education change as well?